Innovative Approaches and Solutions for Climate Resilient and Sustainable Livestock Systems - Nazan Koluman; Yavuzkan Paksoy; Serap Göncü (Archives of Current Research International, 2025)
As the impacts of climate change continue to escalate, ensuring the sustainability and resilience of livestock systems has become a global necessity. Increasingly frequent extreme weather events, shifting precipitation patterns, and the proliferation of pests and diseases are putting immense pressure on conventional livestock practices. These challenges call for a transition to adaptive and climate-resilient approaches that can withstand environmental stressors. Rising temperatures, prolonged droughts, erratic rainfall, and water scarcity are having significant effects on animal health, productivity, and overall farm operations. This issue is especially pressing in Mediterranean regions, where agriculture is highly vulnerable to climate variability. Traditional livestock systems are under growing threat, making immediate and context-specific adaptation strategies essential. In this context, comprehensive climate risk assessments are indispensable tools for identifying regional vulnerabilities and designing appropriate responses tailored to local socio-economic and environmental conditions. This paper outlines the foundational principles of climate-resilient livestock systems, emphasizing sustainability, genetic and ecological diversity, and system adaptability. Key strategies include the use of heat- and disease-tolerant livestock breeds, rotational and adaptive grazing techniques, integrated crop-livestock systems, and improved management practices for pasture, forage, and water resources. These approaches not only enhance resilience but also promote environmental conservation and long-term agricultural viability. Risk management is another critical component. Tools such as weather-indexed insurance, accessible credit, and early warning systems are essential for helping farmers absorb shocks and recover from climate-related losses. Embedding these instruments within national climate adaptation frameworks is vital for ensuring systemic resilience. The paper also presents global case studies illustrating the successful implementation of climate-resilient livestock practices. These examples highlight the importance of innovation, community engagement, and context-specific adaptation. Lessons learned from these cases offer valuable insights that can inform policy and practice across different regions. Furthermore, the role of government policy, international cooperation, and institutional support is discussed. Financial incentives, training programs, and technical assistance are crucial for promoting the widespread adoption of climate-resilient practices. In conclusion, the transition to sustainable and climate-resilient livestock systems is not only an environmental imperative but also a social and economic necessity. It demands coordinated efforts, strategic investment, a strong policy framework at all levels.